Mapping and navigating ontologies in water governance: the case of the Ganges. Issue 7 (16th November 2020) - Campbell, Sam; Gurney, Laura
ABSTRACT: The foregrounding of economic interests to the exclusion of broadly termed 'cultural' interests in water governance has been challenged by the grant of legal personality to rivers, including the Ganges. In this article, we explore the 2017 Ganges judgment of the High Court of Uttarakhand, which conferred legal personality on the river, as a case study which exemplifies the recognition and negotiation of different ontologies of water. We explore the judgment's simultaneous mobilization of the Ganges as socio-economic resource, ecosystem and spiritual being. Our analysis engages with possible tensions between water ontologies, and we ask how ontological conjunctures may be foregrounded, and disjunctures navigated, in practice.